Cobalt Bis(dicarbollide) Alkylsulfonamides: Potent and Highly Selective Inhibitors of Tumor Specific Carbonic Anhydrase IX - Grüner, Bohumír; Kugler, Michael; El Anwar, Suzan; Holub, Josef; Nekvinda, Jan; Bavol, Dmytro; Růžičková, Zdeňka; Pospíšilová, Klára; Fábry, Milan; Král, Vlastimil; Brynda, Jiří; Řezáčová, Pavlína (ChemPlusChem, 2021)
Carbonic anhydrase IX (CAIX) is an enzyme expressed on the surface of cells in hypoxic tumors. It plays a role in regulation of tumor pH and promotes thus tumor cell survival and occurrence of metastases. Here, derivatives of the cobalt bis(dicarbollide)(1-) anion are reported that are based on substitution at the carbon sites of the polyhedra by two alkylsulfonamide groups differing in the length of the aliphatic connector (from C1 to C4, n=1-4), which were prepared by cobalt insertion into the 7-sulfonamidoalkyl-7,8-dicarba-nido-undecaborate ions. Pure meso- and rac-diastereoisomeric forms were isolated. The series is complemented with monosubstituted species (n=2). Synthesis by a direct method furnished similar derivatives (n=2, 3), which are chlorinated at the B(8,8') boron sites. All compounds inhibited CAIX with subnanomolar inhibition constants and showed high selectivity for CAIX. The best inhibitory properties were observed for the compound with n= 3 and two substituents present in rac-arrangement with Ki =20 pM and a selectivity index of 668. X-ray crystallography was used to study interactions of these compounds with the active site of CAIX on the structural level.
Keywords: inhibitory karboanhydras; molekulární konformace; carboranes; Molecular Conformation; Catalytic Domain; carbonic anhydrase IX; Humans; simulace molekulového dockingu; Carbonic Anhydrase IX; komplexní sloučeniny; Molecular Docking Simulation; sulfonamidy; kobalt; krystalografie rentgenová; vazebná místa; karboanhydrasa IX; lidé; Cobalt; Crystallography, X-Ray; Coordination Complexes; Binding Sites; Carbonic Anhydrase Inhibitors; anti-tumor agents; katalytická doména; Neoplasms; nádory; enzyme inhibitors; cobalt; Sulfonamides